THE INFLUENCE OF EYE COORDINATION TRAINING ON CAPTURE SKILLS IN SOFTBALL GAMES ON 2014 PENJASKESREK STUDENTS - Syaranamual, Jusak; Tahapary, Johni Melvin; Lolangluan, Welem Arawaman (Biofaal Journal, 2020)
This study aims to determine: the effect of coordination training on capture throwing skills on student penjaskesrek force 2014. that the student penjaskesrek force 2014 has not been able to throw a good rebound sometimes throws not to friends and throws soar also sometimes passing from a teammate so that the opponent with can easily seize the ball. Population and Sample used in this research is student of Penjaskesrek Study Program class of 2014. The sampling above is based on pertimbanagan cost and time of research. Populations that have been grouped so that the sample of the population is classified as restricted random sample. Furthermore Roscoe in (2000) confirmed the number of sample members for a simple experimental study with a rigorous experimental control to be successful if samples were 10 to 20 people.